BH3-only BIK Regulates BAX,BAK-dependent Release of Ca2+ from Endoplasmic Reticulum Stores and Mitochondrial Apoptosis during Stress-induced Cell Death - Jaigi P. Mathai; Marc Germain; Gordon C. Shore (2005)
BIK, a pro-apoptotic BH3-only member of the BCL-2 family, targets the membrane of the endoplasmic reticulum (ER). It is induced in human cells in response to several stress stimuli, including genotoxic stress (radiation, doxorubicin) and overexpression of E1A or p53 but not by ER stress pathways resulting from protein malfolding. BIK initiates an early release of Ca2+ from ER upstream of the activation of effector caspases. Release of the mobile ER Ca2+ stores in baby mouse kidney cells doubly deficient in BAX and BAK, on the other hand, is resistant to BIK but is sensitive to ectopic BAK. Over-expression of p53 stimulates recruitment of BAK to the ER, and both its recruitment and assembly into higher order structures is inhibited by BIK small interfering RNA. Employing small interfering RNA knockdowns, we also demonstrated that release of ER Ca2+ and mitochondrial apoptosis in human epithelial cells requires BIK and that a Ca2+-regulated target, the dynamin-related GTPase DRP1, is involved in p53-induced mitochondrial fission and release of cytochrome c to the cytosol. Endogenous cellular BIK, therefore, regulates a BAX,BAK-dependent ER pathway that contributes to mitochondrial apoptosis.